2009
DOI: 10.1002/mpr.288
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of an interviewer‐administered version of the Kessler Psychological Distress scale (K10) among Dutch, Moroccan and Turkish respondents

Abstract: The Kessler Psychological Distress scale (K10) is an instrument that is widely used to screen for mental disorders, but information is lacking on its psychometric qualities in non-Western samples. This study used a population-based sample (N = 725) to assess the reliability and validity of the K10 across ethnic groups in an urban area. The results were generally supportive of the K10 as a reliable and valid instrument to screen for anxiety and depression in all three groups. Cronbach's alpha was high (0.93) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
126
2
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 33 publications
9
126
2
10
Order By: Relevance
“…The construct validity of the measure has recently been challenged by Berle et al (2010), who sought to examine two previously reported factor structures in a treatment seeking sample; namely Kessler et al's (2002) single factor model and Brooks et al (2006) four factor model (with two second-order factors). Both structures had previously demonstrated acceptable model fit in large community samples (Brooks et al 2006;Fassaert et al 2009), however Berle et al (2010) found that neither model provided adequate fit to the clinical data, which resulted in the authors concluding that the scoring and interpretation of the scale may need to be revised for such populations depending on the observed structure.…”
Section: Introductionmentioning
confidence: 89%
“…The construct validity of the measure has recently been challenged by Berle et al (2010), who sought to examine two previously reported factor structures in a treatment seeking sample; namely Kessler et al's (2002) single factor model and Brooks et al (2006) four factor model (with two second-order factors). Both structures had previously demonstrated acceptable model fit in large community samples (Brooks et al 2006;Fassaert et al 2009), however Berle et al (2010) found that neither model provided adequate fit to the clinical data, which resulted in the authors concluding that the scoring and interpretation of the scale may need to be revised for such populations depending on the observed structure.…”
Section: Introductionmentioning
confidence: 89%
“…The K-10 is a 10 item measure of psychological distress, with strong evidence supporting the relationship between the K-10 and a diagnosis of anxiety and depressive disorders (Andrews & Slade, 2001). Psychometric studies indicate that the K-10 has excellent internal consistency, even with ethnically diverse populations (˛ = 0.93, Fassaert et al, 2009). In the present sample Cronbach's alpha was high (˛ = 0.79).…”
Section: Sheehan Disability Scales (Sds;mentioning
confidence: 84%
“…Sixth, the psychometric properties of many of the measures employed in the current study have not been examined amongst Arab Australians and, consequently, some caution is needed. However, it is important to note that there is evidence of the reliability and validity of the K-10 and PHQ-9, which was employed in the present study, for the Moroccan and Turkish Dutch (Fassaert et al, 2009) and Saudis (Becker et al, 2002), respectively. Future research would benefit from further and broad psychometric examination of these measures in Arab Australians as well as other cultural and ethnic groups more broadly.…”
Section: Discussionmentioning
confidence: 96%